Struktur Komunitas Fitoplankton di Perairan Teluk Benoa, Bali - Ira Fitriana; Yulianto Suteja; I Gede Hendrawan (Fakultas Kelautan dan Perikanan Universitas Udayana, 2021)
Benoa Bay is a waters that have tourism activities, ship transportation routes and aquaculture. The reasearch of phytoplankton community structure conducted in February 2019. Phytoplankton sampling carried out horizontally by pulling the plankton net using a ship for 5 minutes. The plankton net used has a 30 µm meshsize, 50 cm in diameter and 1.5 meters in length. The composition of phytoplankton species consisted of Bacillariophyceae and Dinophyceae classes. The total abundance of phytoplankton individuals ranged from 268.07 sel/l to 2,500.59 sel/l with an average value 878.87 sel/l. The value range of phytoplankton diversity index was 0,31 to 1,47, with an average value is 0.87. This shows that in general the phytoplankton community has low diversity (H'<1). The phytoplankton uniformity index ranged from 0,14 - 0,58, with an average value is 0,35. This shows that in general the phytoplankton community has low uniformity (E<0.4). The value range of dominance index was 0,31 to 0,89, with an average value is 0.63. This shows that in general the dominance value is high (1>C>0.5). Relatively low uniformity values with relatively high dominance values indicate that the genus found during the study has a non-uniform composition and there is a dominating genus, namely the genus Coscinodiscus from the Bacillariophyceae class.